Emotional Assessment in Spanish Youths With Antisocial Behavior - García-García, Juan; Gil-Fenoy, María José; Sánchez-Barrera, María Blasa; de la Fuente-Sánchez, Leticia; Ortega-Campos, Elena; Zaldívar-Basurto, Flor; Carmona-Samper, Encarna (Frontiers in Psychology, 2021)
Impaired emotional capacity in antisocial populations is a well-known reality. Taking the dimensional approach to the study of emotion, emotions are perceived as a disposition to action; they emerge from arousal of the appetitive or aversive system, and result in subjective, behavioral, and physiological responses that are modulated by the dimensions of valence, arousal, and dominance. This study uses the International Affective Picture System (IAPS) to study the interaction between the type of picture presented (pleasant, neutral, or unpleasant) and group (adolescents under custody in juvenile justice centers, adolescents under non-custodial measures, and secondary school students) in the emotional assessment of these dimensions. The interaction between the study variables was statistically significant. Statistically significant differences were found between the three types of pictures presented, in the ratings of unpleasant pictures between the custody group and the group of secondary students in regular schooling in valence, and in the ratings of unpleasant, neutral, and pleasant pictures in arousal, between the custody group and all groups. Discriminant analyses of each affective dimension indicate that the unpleasant pictures with violent and/or aggressive content tend to be in the functions that most differentiate the antisocial groups.